Comparison of operative methods performed in prophylaxis of female reproductive organs descensus - Grześko, Joanna; Elias, Marek; Gabryś, Marian Stanisław; Tłaczała, Magdalena (Menopause Review/Przegląd Menopauzalny, 2006)
supracervical hysterectomy, total abdominal hysterectomy, urine incontinence